AESTHETICS OF MAKEUP AND COSTUME DESIGN IN THE DANCE "CISONDARI": UNVEILING LOCAL CULTURAL IDENTITY - Tifan Muhammad Amirulloh; Saian Badaruddin (Journal of Dance and Dance Education Studies, 2024)
This study aims to reveal the values and meanings embedded in the makeup and costume design of the dance piece "Cisondari," choreographed by Tifan Muhammad Amirulloh. Created in 2019, this dance work serves as the choreographer's tribute to the culture of Cisondari Village, incorporating local elements as its main performance components. Makeup and costume design are not merely aesthetic elements but also act as mediums to convey cultural identity and character traits within the dance. This research employs a qualitative descriptive method, using observation, in-depth interviews with the choreographer and costume designer, as well as visual documentation. Data analysis techniques include data reduction, data display, and conclusion drawing to identify the symbolic meanings of the makeup and costumes in this dance. The results show that makeup in the "Cisondari" dance emphasizes bold facial expressions to depict the character's identity and strength, aiming to help the audience understand the dancer's role, even from a distance. The costume design, inspired by the history and unique features of Cisondari Village, highlights visual elements that reflect local wisdom and cultural identity. The combination of makeup and costume in the "Cisondari" dance conveys profound symbolic meaning, illustrating cultural values and enhancing the overall aesthetic of the performance.